At-Tadakhkhul al-Lughawī min al-Lughah al-‘Arabiyyah ilā al-Lughah al-Indūnīsiyyah fī Tarjamah al-Qur’ān min Wizārat ash-Shu’ūn ad-Dīniyyah al-Indūnīsiyyah - Rizky Hanivan; Mohammad Arif Setyabudi (Program Studi Pendidikan Bahasa Arab, 2022)
The use of Arabic and Indonesian can theoretically cause symptoms of mutual influence between Arabic and Indonesian which is characterized by the use of Arabic elements in the translation of the Qur'an. It is assumed to interfere with translation and make it difficult for the reader to deduce meaning. This difficulty can ultimately lead to errors in concluding the intent of the verse. This is what prompted us as researchers to be interested in studying the problem more deeply in a thesis writing. The purpose of this study is to know the interference of Arabic language in The Indonesian language in the Qur'an Translation of the Ministry of Religious Affairs of the Republic of Indonesia and to know the various language interferences contained in the Qur'an. This research was conducted with literature studies with a descriptive approach. Found that there is interference of Arabic into Indonesian in the Translated Qur'an. interference from Arabic into Indonesian can occur. Interference in the translation includes four types: Phonemic, phonic, morphological, and lexical. There is a grammatical inability of Indonesian language in translation because of the difficulty of finding the right translation editor and common to the rules of Indonesia languange.